Observational study of HSG with laparoscopic correlation in infertility patients - Dubbewar, Avinash; Nath, Saumen Kanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Uterine abnormalities contribute to 10% of infertility cases and 50% of women with recurrent early pregnancy loss whereas fallopian tube abnormalities contribute to 20% of such cases. Methods: Total 61 patients of infertility and subfertility undergoing evaluation and treatment at our centre were selected for HSG. Total 25 patients from this group have undergone diagnostic laparoscopy, their findings were correlated with HSG findings retrospectively. Results: All the patients in the study group were either primary or secondary infertility patients. Of the 61 patients of infertility, 49 were in primary infertility group and 12 were in secondary infertility group. The age of patients was between 23 and 35 years. The average duration of primary infertility was 5 years and secondary infertility was 3.5years. Total 61 patients underwent HSG, 42(68.8%) patients had normal findings and 19(31.14%) patients had abnormal findings. In abnormal findings 4(6.55%) were Mullerian abnormalities and 15(24.59%) were either unilateral or bilateral tubal block. Total 25 patients underwent diagnostic laparoscopy out of 61 patients. The sensitivity of HSG was 90% and specificity was 60 % with positive predictive value of 60% and negative predictive value of 90% as compared to diagnostic laparoscopy. Tubal block was defined as any form of tubal occlusion detected at HSG and finally confirmed on laparoscopy. In our laparoscopy findings, peri-adnexal adhesions were found in 5 (20%) of the blocked tubes on laparoscopy. Endometriosis was detected in 1 (4%) of the blocked tubes and suspected intra-tubal block in 2 (8%).Pelvic inflammatory disease was found to contribute in 3 (12%). Conclusions: HSG demonstrates high sensitivity in our study. So, it should be used as the initial investigation for identifying uterine abnormality and tubal patency. As the specificity is less, we suggest that laparoscopy is necessary to recognize those cases of tubal block, which were unrecognized or wrongly recognized on HSG. In addition, the patients who were found to have tubal block on HSG, laparoscopy helps in finding the cause of infertility like existence of peritubal adhesions and endometriosis that can guide appropriate therapy.